Whip spiders (Amblypygi, Arachnida) of the Western Palaearctic—a review - Blick, Theo; Seiter, Michael (Zootaxa, 2016)
All records of the two amblypygid species occurring in the Western Palaearctic are mapped and both species (Charinus ioanniticus and Musicodamon atlanteus) are discussed. Charinus ioanniticus is known from the Eastern Mediterranean (Greece, Turkey, Israel and Egypt) from 10 localities and Musicodamon atlanteus is known from the Maghreb (Morocco, Algeria) from three localities. All records are mapped.